Resolution in QCM Sensors for the Viscosity and Density of Liquids: Application to Lead Acid Batteries - Jorge Marcos-Acevedo; José Fariña; Loreto Rodríguez-Pardo; Ana María Cao-Paz (Sensors, 2012)
In battery applications, particularly in automobiles, submarines and remote communications, the state of charge (SoC) is needed in order to manage batteries efficiently. The most widely used physical parameter for this is electrolyte density. However, there is greater dependency between electrolyte viscosity and SoC than that seen for density and SoC. This paper presents a Quartz Crystal Microbalance (QCM) sensor for electrolyte density-viscosity product measurements in lead acid batteries. The sensor is calibrated in H2SO4 solutions in the battery electrolyte range to obtain sensitivity, noise and resolution. Also, real-time tests of charge and discharge are conducted placing the quartz crystal inside the battery. At the same time, the present theoretical “resolution limit” to measure the square root of the density-viscosity product ( ) of a liquid medium or best resolution achievable with a QCM oscillator is determined. Findings show that the resolution limit only depends on the characteristics of the liquid to be studied and not on frequency. The QCM resolution limit for measurements worsens when the density-viscosity product of the liquid is increased, but it cannot be improved by elevating the work frequency.